Development of intelligent protection and automation control systems using fuzzy logic elements - Ansabekova, Gulbakyt; Sarsikeyev, Yermek; Abdimuratov, Zhubanyshbai; Appakov, Nurbol; Kaliyev, Zhanybek; Umurzakova, Anara; Sarbassova, Nurbanu; Zhumatova, Assel (Institute of Advanced Engineering and Science, 2024)
In this article, the causes of technological disturbances in electrical systems are considered, and several characteristic disadvantages of the protection and automation of elements of electrical systems are highlighted. The tendency to decrease the reliability of relay protection associated with the transition from analog to digital types of protection is substantiated. Based on the studied examples, the use of fuzzy logic in protections, the expediency of using fuzzy logic elements in protection devices, and the automation of electrical systems to identify types of short circuits are justified. This article analyzes the most common damages and presents the results of modeling an electrical system with transformer coupling, where all types of asymmetric short circuits were initiated. The dynamics of changes in the symmetrical components of short-circuit currents of the forward, reverse, and zero sequences are determined. Rules have been created for the identification of asymmetric types of short circuits. An algorithm of protection and automation operation using fuzzy logic elements has been developed. The proposed algorithm of protection and automation will reduce the time to determine the type of damage and trigger protections.